ENVIRONMENTAL RESPONSE OF EARLY PERMIAN VOLCANISM IN HONGLIUHE AREA ON THE BORDER BETWEEN XINJIANG AND GANSU PROVINCES - Pan J.H.; Guo Z.J.; Liu C.; Zhang Y. (My University, 2007)
The early Permian basalts in Hongliuhe area on the Border between Xinjiang and Gansu Provinces are interbedded with limestone, and a small amount of limestone are filled in the triangle gap of pillow basalts. The carbon and oxygen isotopic composition of carbonates in intermittent volcanic eruption period and rapid volcanic eruption period are significantly different, respectively, δ13C and δ18O are 3.2‰ and -14.2‰ in average in interbedded limestone which is partially positive, -0.7‰ and - 14.2‰ in average in limestone among pillow basalts which is partially negative. The research of carbon and oxygen stable isotope shows that environment variation in the marine basin is influenced greatly by volcanic eruption.
Keywords: CARBON AND OXYGEN ISOTOPE; CARBONATE ROCK; EARLY PERMIAN; ENVIRONMENTAL RESPONSE; VOLCANISM; Permian; Paleozoic::Permian; Палеозой::Пермская